2000
DOI: 10.1007/s11906-000-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension: A possible target for antihypertensive medication

Abstract: Vascular changes associated with elevated blood pressure may precede the clinical diagnosis of hypertension. Even after the diagnosis is made, associated coronary heart disease and renal disease continue to progress, despite adequate blood pressure control. Early treatment of blood pressure may reduce the incidence of clinical hypertension and reduce the long-term consequences of hypertension. Animal studies have shown that early blood pressure lowering, through blockade of the renin-angiotensin system, preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Trial of Preexisting Hypertension (TROPHY) is a 4-year multicenter, double-blind, placebo-controlled study of 30-to 65-year-olds with blood pressure between 130 and 139 mm Hg systolic and between 85 and 89 mm Hg diastolic randomized to 2 years of treatment with candesartan or placebo and then followed for 2 additional years on placebo alone (all are treated with lifestyle interventions) [4]. This study will test whether early drug treatment can interrupt the progression of prehypertension to hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Trial of Preexisting Hypertension (TROPHY) is a 4-year multicenter, double-blind, placebo-controlled study of 30-to 65-year-olds with blood pressure between 130 and 139 mm Hg systolic and between 85 and 89 mm Hg diastolic randomized to 2 years of treatment with candesartan or placebo and then followed for 2 additional years on placebo alone (all are treated with lifestyle interventions) [4]. This study will test whether early drug treatment can interrupt the progression of prehypertension to hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a treatment trial called TROPHY (Trial of Preventing Hypertension), enrolling subjects with prehypertensive levels of blood pressure (systolic 130-139 mm Hg), is addressing the issue of pre-emptive ARB treatment in reducing the development of hypertension [17].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…9,[15][16][17][18][19][20] Even small, persistent reductions of just a few mm Hg in average BP have the potential to avoid large absolute numbers of premature deaths and disabling strokes in the long term. 9,17 Vascular changes that occur during cardiovascular disease generally precede the onset of hypertension and often continue even after hypertension is diagnosed and controlled, [21][22][23][24] Early, aggressive and sustained BP lowering has the potential to reduce progression from pre-hypertension to hypertension, 25,26 to reduce progression to more severe hypertension, 27 and to reduce long-term cardiovascular consequences. 18,25,27 A meta-analysis of seven clinical trials examining the benefits of anti-hypertensive therapy in more than 26 000 patients showed that hypertension progressed from moderate (SBP 140-179; DBP 90-109 mm Hg) to severe (SBP4180 mm Hg; DBP4110 mm Hg) in only 0.7% of patients receiving active treatment vs 11.2% in the placebo group.…”
Section: Introductionmentioning
confidence: 99%